HUBUNGAN KELERENGAN DENGAN KADAR AIR TANAH, PH TANAH, DAN PENAMPILAN JERUK GERGA DI KABUPATEN LEBONG - Nurlina Banjarnahor; Kanang Setyo Hindarto; Fahrurrozi Fahrurrozi (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2018)
[RELATIONSHIP OF SLOPE STEEPNESS TO SOIL WATER CONTENT, SOIL PH, AND PERFORMANCES OF GERGA ORANGE AT LEBONG REGENCY]. In Lebong Regency, gerga orange is commonly grown in hilly areas and many of the crop stands were found on steep sloped land. Objective of this study was to determine the pattern of relationship of slope steepness to soil water content, soil pH, and the overall plant performances. Soil samples were collected from the area below the canopy of 300 gerga orange trees differing in the slope steepness for for soil water content (SWC) and soil pH. The observation of plant performances were also made from the same tree as used for the soil properties observations. The analysis of regression indicated that relationship of slope steepness to both the observed soil properties and plant performances could be represented by the linear models suggesting that all the observed variables were reduced along with the increasing slope steepness.